1988
DOI: 10.1080/03610738808259746
|View full text |Cite
|
Sign up to set email alerts
|

The problem of naming in SDAT: A relative deficit

Abstract: Research relating to language disorder in senile dementia of the Alzheimer type (SDAT) has focused primarily on naming impairment, formally termed anomia or nominal aphasia/dysphasia. Data resulting from this research have been insufficiently informed by a comparative linguistic framework in which performance on naming tasks is contrasted with performance on other forms of language tasks. The present study involves the comparison of 21 adults with SDAT and 18 demographically controlled normal elderly adults on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…Analysis of the seven subtests of the Western Aphasia Battery revealed that both vascular samples had deficits at the 0.0001 level when compared with normal elderly persons on the word fluency task, which is a metanaming [37] task assessing capability for generative naming (e.g., bname as many foods as you canQ). The infarct sample was also impaired at the 0.0001 level when compared to normal elderly on reading comprehension and sequential commands tasks, whereas the noninfarct sample was impaired in relation to normals on these tasks at the 0.004 and 0.0004 levels ( Table 4).…”
Section: Language Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the seven subtests of the Western Aphasia Battery revealed that both vascular samples had deficits at the 0.0001 level when compared with normal elderly persons on the word fluency task, which is a metanaming [37] task assessing capability for generative naming (e.g., bname as many foods as you canQ). The infarct sample was also impaired at the 0.0001 level when compared to normal elderly on reading comprehension and sequential commands tasks, whereas the noninfarct sample was impaired in relation to normals on these tasks at the 0.004 and 0.0004 levels ( Table 4).…”
Section: Language Measuresmentioning
confidence: 99%
“…Comparisons between both vascular samples and normal elderly on repetition and auditory comprehension were also statistically significant (Table 4). There were no significant differences between either the infarct or noninfarct patients in relation to normal elderly persons on oral language tasks of responsive speech and sentence completion, which are the least complex of language tasks involving overlearned language sequences (e.g., broses are red, violets are what?Q) [33][34][35]37].…”
Section: Language Measuresmentioning
confidence: 99%
“…Oral language processing was measured by six subtests from the Western Aphasia Battery (WAB; Kertesz, 1982) and by the Boston Naming Test (BNT; Kaplan et al, 1983). Oral language variables assessed were repetition, naming, auditory verbal comprehension, and grammatical-syntactic processing (Emery, 1985(Emery, ,1986(Emery, ,1993(Emery, ,1996Emery & Breslau, 1988Kertesz, 1979Kertesz, , 1982Yngve, 1986). The WAB Repetition test requires the participant to repeat 14 items.…”
Section: Other Cognitive Measuresmentioning
confidence: 99%
“…Despite the negative findings summarized above, therefore, it is perhaps not surprising that other evidence suggests a degree of vulnerability of articulatory and phonological processing (Hart, 1988). An abnormal rate of phonological errors has been either occasionally noted, or even specifically investigated and reported, both in spontaneous speech (Gavazzi, Luzzatti, & Spinnler, 1986;Loebel, Dager, Berg, & Hyde, 1990;Shuren, Geldmacher, & Heilman, 1993) and in more formal word and sentence production tasks (Biassou et al, 1995;Emery & Breslau, 1988;Glosser, Friedman, Kohn, Sands, & Grugan, 1998;Glosser, Kohn, Friedman, Sands, & Grugan, 1997;Obler & Albert, 1984;Price et al, 1993). Because phonological and/or articulatory disruption is characteristic of several other neurodegenerative diseases which may be contenders in the differential diag- (Cummings, Darkins, Mendez, Hill, & Benson, 1988;Gordon & Illes, 1987;Hier, Hagenlocker, & Shindler, 1985;Holland, McBurney, Moossy, & Reinmuth, 1985)], if reported speech output deficits in probable AD were infrequent, and only referred to cases lacking pathological confirmation, one might question whether such deficits were actually associated with non-Alzheimer pathology in cases which had accidentally been included in a probable AD group.…”
mentioning
confidence: 97%